A Review of Ongoing Trials of Stereotactic Ablative Radiotherapy for Oligometastatic Cancers: Where Will the Evidence Lead? - Al-Shafa, Faiez; Arifin, Andrew J.; Rodrigues, George B.; Palma, David A.; Louie, Alexander V. (Frontiers in Oncology, 2019)
Purpose: The oligometastatic state is a proposed entity between localized cancer and widely metastatic disease, comprising an intermediate subset of metastatic cancer patients. Most data to support locally-directed treatment, such as stereotactic ablative radiotherapy (SABR), for oligometastases are from retrospective institutional reports. Following the success of a recently completed and reported phase II trial demonstrating important clinical outcomes, herein we review the current landscape of ongoing clinical trials in this context. Materials and methods: A review of currently activated and registered clinical trials was performed using the clinicaltrials.gov database from inception to February 2019. A search of actively recruiting trials, using the key words oligometastases, SABR, and various related terms was performed. Search results were independently reviewed by 2 investigators, with discrepancies settled by a third. Data abstracted from identified studies included study type, primary disease site, oncologic endpoints, and inclusion/exclusion criteria. Results: Of the initial 216 entries identified, 64 met our review eligibility criteria after full-text review. The most common study type was a Phase II clinical trial (n=35, 55%) with other study designs ranging from observational registry trials to Phase III randomized controlled trials. A minority of trials were randomized in design (n=17, 27%). While most studies allowed for metastases from multiple primary disease sites (n=22, 34%), the most common was prostate (n=13, 15%), followed by breast, gastrointestinal, non-small cell lung cancer and renal (n=6, 9% each). In studies with a solitary target site, the most common was liver (n=6, 9%) followed by lung (n=3, 5%). The most common primary endpoints were progression-free survival (n=20, 31%) and toxicity (n=10, 16%). A combined strategy of systemic therapy and SABR was an emerging theme (n=23, 36%), with more recent studies specifically evaluating SABR and immunotherapy (n=9, 14%). Conclusion: The safety and efficacy of SABR as oligometastasis-directed treatment is increasingly being evaluated within prospective clinical trials. These data are awaited to compliment the abundance of existing observational studies and to guide clinical decision-making.